Branched Bio‐Lubricant Base Oil Production through Aldol Condensation. Issue 21 (23rd October 2019) - Norton, Angela M.; Liu, Sibao; Saha, Basudeb; Vlachos, Dionisios G.
Abstract: Invited for this month′s cover is the group of Dionisios G. Vlachos at the Catalysis Center for Energy Innovation, University of Delaware. The cover design shows the application of renewable feedstocks to make a lubricant base oil that can be used in a racecar. The Full Paper itself is available at 10.1002/cssc.201901838 . Abstract : "an average pit stop for an IndyCar takes 10 seconds or less…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201901838 . View the Front Cover here: 10.1002/cssc.201902794 .